DISEMINASI TEKNOLOGI PENGEMASAN UNTUK MENINGKATKAN DAYA SAING PRODUK OLAHAN PANGAN PADA “KWT SRI TANJUNG”, SUKOSARI, KASEMBON, MALANG - Suprayogi Suprayogi; Nimas Mayang Sabrina; Muhammad Syamsul Hadi; Izzati Ardhan Firdausyi; Isnan Nurdiansyah; Khosid Mahendra Ismail; Ferdyandika Putra Aprilia One; Hikmat Avisenna; Muhamad Toha (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Sukosari Village is one of the villages in Kasembon District which has great potential in agriculture. In Sukosari Village, there is a Kelompok Wanita Tani (KWT) called KWT “Sri Tanjung” which has been producing food processing and agricultural handicrafts. Processed food products that have been produced and marketed are corn, cassava, and gadung chips, and packaged drinks called "Jaselang". These products have been packaged in good packaging and following the packaging requirements of food products. However, due to a large number of competitors with attractive packaging, this KWT member felt that packaging was one of the important things in attracting buyers. Another problem faced by partners is that so far they have done the packaging manually, there is no packaging machine used to package the food products produced. Thus, the purpose of Doktor Mengabdi program is to transfer knowledge related to packaging technology and provide assistance in the product packaging process. The method used in this activity is counseling and assistance related to food product packaging technology. Also, because in this activity two packaging machines were donated, namely an automatic bottle closing machine and a horizontal band sealer machine, the practice of using both machines was carried out. The results of this activity show that the empowerment activities are going well, KWT members have good knowledge of packaging technology. In addition, the existence of two packaging machines that were donated further increased their productivity.